Conservation of the critically endangered Achondrostoma occidentale (Pisces: Cyprinidae): integrating habitat data in restocking programs to improve population recovery - D, Mameri; C, Sousa Santos; MF, Magalhães; JI, Robalo (Gaia Scientia, 2016)
Cyprinid fauna endemic to the Iberian Peninsula is currently facing several human-caused threats which enhance their risk of extinction. The populations of the critically endangered Achondrostoma occidentale, occurring only in three small and intermittent Portuguese river basins, have been reinforced with fish bred ex-situ in order to minimize their risk of extinction. This study aimed to describe the restocking actions conducted and to identify and characterize the summer refugia that should become targets for restoration and further restocking. The results evidence population increments and a high representativeness of younger age classes in the restocked populations. The importance of annual monitoring of fish abundance to assess how the species is coping with the stochastic and deterministic stressors that may eventually compromise its survival is highlighted.